Analyzing the Philosophy of Mangan Ora Mangan Sing Penting Kumpul in Promoting Social Solidarity and Addressing Social Inequality - Nando, Fikri; Arifudin, Arifudin; Qilya Alrizis, Muhamad Omar (Jurnal Sosiologi Reflektif, 2024)
Social disintegration resulting from discrimination and social inequality remains a persistent issue in various societies, including within the context of Javanese communities. The philosophy of Mangan Ora Mangan Sing Penting Kumpul (whether we eat or not, what matters is to gather) represents a cultural value that can strengthen social solidarity and address the problem of social segregation. This study aims to analyze this philosophy through the lens of social solidarity and explore its potential as an alternative social movement for the lower-class communities. This research employs a qualitative approach using hermeneutic methods to interpret Javanese cultural texts within their socio-historical context. Data were gathered from primary sources such as journals and books, as well as secondary literature relevant to the research topic. The data analysis is grounded in Marx’s dialectical historical materialism and Neo-Marxist theory, specifically focusing on social solidarity and grassroots movements. The findings reveal that the philosophy of Mangan Ora Mangan Sing Penting Kumpul plays a crucial role in promoting social solidarity within Javanese society, particularly in response to economic and social pressures. This philosophy not only fosters communal unity but also emphasizes the importance of equality and cooperation in confronting social injustice. As such, it holds significant potential to be developed as an inclusive social movement, centered on community values and collective welfare. Disintegrasi sosial akibat diskriminasi dan ketimpangan sosial masih menjadi persoalan di berbagai masyarakat, termasuk dalam konteks masyarakat Jawa. Filosofi Mangan Ora Mangan Sing Penting Kumpul menjadi salah satu nilai budaya yang dapat memperkuat solidaritas sosial dan mengatasi masalah segregasi sosial. Penelitian ini bertujuan untuk menganalisis filosofi tersebut dalam perspektif solidaritas sosial, serta mengeksplorasi potensi filosofi ini sebagai gerakan sosial alternatif di kalangan masyarakat kelas bawah. Penelitian ini menggunakan pendekatan kualitatif dengan metode hermeneutik untuk memahami teks-teks budaya Jawa dalam konteks sosial-historis. Data dikumpulkan melalui kajian pustaka, baik dari sumber primer seperti jurnal dan buku, maupun sumber sekunder yang relevan dengan topik penelitian. Analisis dilakukan melalui pendekatan dialektika materialisme historis Marx dan teori Neo-Marxisme, khususnya terkait solidaritas sosial dan gerakan masyarakat akar rumput. Hasil penelitian menunjukkan bahwa filosofi Mangan Ora Mangan Sing Penting Kumpul memainkan peran penting dalam mempromosikan solidaritas sosial di kalangan masyarakat Jawa, khususnya dalam menghadapi tekanan ekonomi dan sosial. Filosofi ini tidak hanya memperkuat kebersamaan dalam komunitas, tetapi juga menekankan pentingnya kesetaraan dan kerjasama dalam menghadapi ketidakadilan sosial. Dengan demikian, filosofi ini memiliki potensi untuk dikembangkan sebagai bentuk gerakan sosial yang inklusif, berfokus pada nilai-nilai komunitas dan kesejahteraan bersama.